Percutaneous nephrolithotomy in England: practice and outcomes described in the Hospital Episode Statistics database. (21st November 2013) - Armitage, James N.; Withington, John; van der, Jan; Cromwell, David A.; Glass, Jonathan; Finch, William G.; Irving, Stuart O.; Burgess, Neil A.
<x xml:space="preserve">Abstract</x> Objective To investigate the postoperative outcomes of percutaneous nephrolithotomy (PCNL) in English National Health Service (NHS) hospitals. Patients and Methods We extracted records from the Hospital Episode Statistics (HES) database for all patients undergoing PCNL between March 2006 and January 2011 in English NHS hospitals. Outcome measures were haemorrhage, infection within the index admission, and rates of emergency readmission and in‐hospital mortality within 30 days of surgery. Results A total of 5750 index PCNL procedures were performed in 165 hospitals. During the index admission, haemorrhage was recorded in 81 patients (1.4%), 192 patients (3.8%) had a urinary tract infection (UTI), 95 patients (1.7%) had fever, and 41 patients (0.7%) had sepsis. There were 595 emergency readmissions in 518 patients (9.0%). Reasons for readmission were varied: 70 (1.2%) with UTI, 15 (0.3%) sepsis, 73 (1.3%) haematuria, 25 (0.4%) haemorrhage, and 25 (0.4%) acute urinary retention. There were 13 (0.2%) in‐hospital deaths within 30 days of surgery. Conclusions Haemorrhage and infection represent relatively common and potentially severe complications of PCNL. Mortality is extremely rare after PCNL (about one in 400 procedures overall) but almost one in 10 patients have an unplanned hospital readmission within 30 days of surgery. Complications of PCNL may be under‐reported in the HES database and need to be corroborated using other data sources.